Fast and Lightning-fast Development Paths for Cloud Startups: cases from Israel and the USA - Grażyna Golik-Górecka (Communications of International Proceedings, 2023)
The aim of the article is to present the concept as well as the stages and strategies of fastscaling and blitzscaling, i.e. very fast and rapid growth, along with practical examples of startups operating abroad in the cloud. Research method. To achieve this goal, the applied method consisted in analyzing the literature related to these issues and the method of case studies. They will enable the presentation of evolution through scaling: classic scaling, scaleup, blitzscaling and fastscaling, and also made it possible to indicate conclusions and scientific reflections on understanding the startup strategy in the cloud. These studies allowed to analyze the individual stages of the scaling path and to compare the evolution of thes two cases. In addition, this analysis of case studies illustrates and demonstrates the understanding of current theories in real current conditions and convinces of the very high importance of the phenomena studied. Therefore, three research questions were formulated: 1. Will the innovations of enterprises - digital startups and technologies of the future as well as the form of cloud activity ensure their further international competitiveness?2. Do the scaling phases and strategies support changes in the business model, innovation, or did the discussed companies also achieve the expected above-average growth?3. Do cloud startups properly implement their goals and strategy synergy by going through four types of merging from scaling, scaleup, fastscaling and blitzscaling?To answer these questions, a case study of international start-ups based in Israel and the USA will be analyzed. The analyzes of the development of practical startups carried out above also have value for practitioners, students and scientists.
Keywords: start-up; type of scaling: classical scaling; scaleup; fast scaling and blitzscaling; innovation business model and cloud strategy